Äitiysneuvolassa työskentelevien ammattilaisten käsityksiä inkontinenssin ennaltaehkäisystä ja hoidosta - Tuulia Lahtinen; Marjaana Jones; Tiina Vaittinen; Pilvikki Absetz (Sosiaalilääketieteellinen Aikakauslehti, 2026)
The prevention and treatment of incontinence within maternity clinic services is significant from both individual and societal perspectives. Incontinence causes health and social disadvantages for individuals, but it also contributes to environmental burden and economic costs for society. These negative impacts can be reduced by investing in measures of early prevention and treatment. In this article, we examine how health care professionals working in maternity clinics describe the prevention and treatment of incontinence. The data consists of individual and group thematic interviews (n = 17) conducted in 2024 with maternity clinic professionals. The data were analyzed using thematic analysis. Based on the analysis, we identified three themes that illustrate the prevention and treatment of incontinence in the maternity clinic context. The results showed that the initiation of discussion regulates prevention and access to care, pelvic floor health is grounded in knowledge, and the multidisciplinary care pathway for incontinence appears inconsistent. Pregnant and postpartum individuals should have access to preventive pelvic floor physiotherapy services in accordance with recommendations, as well as to high-quality care at an early stage. Preventing and treating incontinence promotes the health of pregnant and postpartum individuals and may also reduce the national economic costs of incontinence and the waste generated by incontinence products. The results can be utilized in the multidisciplinary development of maternity clinic services.